Influence of Mindfulness-Based Stress and Pain Reduction on Psychological Well-being among Preoperative Patients - Shahul Hameed K. P (International Journal of Research in Medical Surgical Nursing, 2025)
Preoperative anxiety and stress are common emotional responses in people awaiting surgery. These psychological issues can increase pain perception, slow down recovery after surgery, and raise the need for pain medication. Mindfulness-Based Stress Reduction (MBSR), an evidence-supported program that combines meditation, focused breathing, and body awareness, has been shown to effectively reduce emotional distress and improve mental stability. Many studies highlight the positive effects of mindfulness in lowering anxiety and enhancing overall psychological health across different groups. The present study seeks to determine the impact of mindfulness-based stress and pain reduction on the psychological well-being of preoperative patients. A randomized controlled trial will be conducted among 60 patients aged 25–60 years, randomly divided into experimental and control groups of 30 each. The experimental group will undergo structured mindfulness sessions over three consecutive preoperative days, whereas the control group will receive standard nursing care. Data will be gathered using validated instruments, including the State-Trait Anxiety Inventory (STAI), the Visual Analogue Scale (VAS), and the WHO-5 Well-being Index. A purposive sampling method will be used to recruit suitable participants. Both descriptive and inferential statistical methods will be utilized with appropriate parametric and nonparametric tests. It is anticipated that patients exposed to mindfulness-based interventions will exhibit a marked reduction in preoperative anxiety and pain, along with enhanced psychological well-being and preparedness for surgery. The outcomes of this study are expected to contribute valuable evidence for integrating mindfulness-based nursing practices into routine preoperative care, thus supporting holistic management and improving surgical outcomes.